Implementasi prinsip negara hukum dalam sistem ketatanegaraan indonesia berdasarkan uud 1945 - APAL, FURQAN (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of the principle of the rule of law in the Indonesian constitutional system based on the 1945 Constitution of the Republic of Indonesia. The rule of law is a fundamental principle that places law as the highest basis in state administration, so that every government action must be in accordance with applicable legal norms. Through a normative juridical research method with a regulatory approach, conceptualization, and analysis of Constitutional Court decisions, this study examines the extent to which the principle of the rule of law is applied in Indonesian constitutional practice. The results of the study indicate that normatively, the principle of the rule of law has been realized through strengthening the checks and balances mechanism, the establishment of supervisory institutions, and the application of the rule of law in various sectors. However, its implementation still faces several obstacles, such as regulatory disharmony, bureaucratic maladministration, and weak integrity of law enforcement officers as conveyed in reports from official institutions such as the Constitutional Court, the Indonesian Ombudsman, the Corruption Eradication Commission, and the National Agency for the Prosecution of State Property. This study concludes that although the structure of the rule of law has been well established, its implementation in practice still requires systematic improvement through regulations, strengthening the authority of state institutions, and increasing the effectiveness of oversight so that the ideals of a rule of law as stated in the 1945 Constitution can be optimally realized.